Scheduling time-sensitive IP traffic - Sousa, Pedro (2003)
This article presents an hybrid priority queuing model based scheduler for real-time traffic differentiation. The proposed scheduler is designed as a mechanism to provide queuing delay differentiation among real-time traffic classes. The novel characteristic of the presented scheduler is the capability to simultaneously try to achieve an upper time limit for queuing delays and, under heavy load conditions, deny class starvation by providing an expectable differentiation schema for excess queuing delays. The attractiveness of the proposed scheduler is its hybrid differentiation capabilities based on a simple queue selection procedure. Additionally, the enhanced differentiation behavior of the scheduler is also highlighted as three distinct configuration modes are possible.